Combining Learner Autonomy and Authentic Written Texts for the Acquisition of Business English Terminology - Gajšt, Nataša (Journal of NELTA, 2014)
Learning of Business English at tertiary level comprises the acquisition of specific linguistic and general competences together with the ability to learn the language autonomously. This paper presents the results of a study conducted with 123 first-year university-level students of Business English engaged in autonomous learning of business-related terminology by reading authentic business news over a period of five months. The data were collected over three academic years. The students were asked to rate the improvement of their linguistic competence, their attitudes towards autonomous learning and the use of authentic resources, and their improvement of the knowledge of business topics. The results showed that the students approved of reading authentic texts of their own choice as a way to develop their competences. The implication of this study is that autonomous learning should be encouraged and that authentic news articles are a good way to motivate students to learn Business English. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10331 Journal of NELTA, Vol 18 No. 1-2, December 2013; 65-76